ANALISIS KESALAHAN BERBAHASA KARYA TULIS NON ILMIAH SISWA SMA KOTA JAMBI - Irma, Ade; Rasdawita; Bambang, Siti Enik Mukhoiyaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines language errors in non-scientific written works in the form of short stories written by Phase F students at SMA Negeri 9 Kota Jambi. The problem underlying this research is the presence of language errors that affect the clarity, accuracy, and effectiveness of students’ writing. This study aims to identify and describe the types of language errors, including aspects of phonology, morphology, syntax, semantics, and spelling. This research employs a qualitative descriptive method. The data consist of 31 short story texts written by students. Data collection techniques include documentation and note-taking. The results show that language errors are still frequently found in students’ writing. Based on the analysis, there are 100 errors in the phonological aspect, 108 errors in the morphological aspect, 101 errors in the syntactic aspect, 37 errors in the semantic aspect, and the highest number of errors occurs in the spelling aspect, with a total of 1,147 errors. Based on these findings, it can be concluded that students’ mastery of linguistic rules still needs improvement. Therefore, efforts are needed to enhance the quality of Indonesian language instruction, provide intensive writing practice, and emphasize the use of proper and correct language rules in order to optimally improve students’ language skills.